Creativity in discourse of navigation health theory - I. M. Kyshtymova (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
In the context of the commercialization of health services and orientation mass media communications processes toward the formation of a consumer society, it becomes important to realize the personal responsibility for their own health and the ability to organize the living environment, maintain an active and meaningful existence. The topicality of culturological and psychological approaches to researches of health, productivity of navigation health theory has been proved in this article. The creativity has been taken up as a cause and effect of human health. As illustrated, the main condition to develop creativity is inculturation. The empiric results of dynamics of schoolchildren's creativity have been shown in the context of study organization in accordance with inculturation principles.